Smartphone - Based Apk Sociologi.Q Learning Media to Improve Students' High Order Thinking Skills (Hots) - Jerry Puspitasari; Joko Sutarto; Suwito Eko Pramono; Yeri Sutopo (Universitas Negeri Semarang, 2023)
The purpose of this research is to improve students' higher order thinking skills (HOTS). The formulation of the problem is to design a prototype and examine the effectiveness of using instructional media. The method used is quantitative. Research results: 1) According to media theory, the application of learning media is new media in the world of education. The Sociology.Q learning media apk is specially designed according to the learning needs of students. 2) The use of this learning media has advantages and disadvantages. 3) The effectiveness of learning media is very effective in learning. The end result is that using smartphone- based learning media at this time can improve students' higher-order thinking skills (HOTS).